Genetic Polymorphisms : an Integrated Approach - Clinton, Vince (United States : Murphy & Moore Publishing, 2021)
The simultaneous occurrence of two or more discontinuous alleles or genotypes in a population is termed as genetic polymorphism. Most genetic polymorphisms are silent and do not interfere with the expression or function of a gene. Polymorphisms are classified into single nucleotide polymorphisms, small scale insertions and deletions, polymorphic repetitive elements, and microsatellites. The single nucleoid changes which happen in the genome in a particular location are termed as single nucleoid polymorphisms (SNPs). They are associated with both coding and non-coding regions. In humans, more than 100 million SNPs have been recognised. This book covers in detail some existent theories and innovative concepts revolving around genetic polymorphisms. It includes some of the vital pieces of work being conducted across the world, on various topics related to genetic polymorphism. Those in search of information to further their knowledge will be greatly assisted by this book.
Includes index.
Includes bibliographical references.
Keywords: Human Genetics; Genetic polymorphisms; Human population genetics; Gene frequency; DNA -- Analysis; Genetic engineering